AROMA (AGU Robotic Optical Monitor for Astrophysical Objects) - Ichiro Takahashi; Kosuke Tsunashima; Takayuki Shiraki; Toru Kojima; Atsumasa Yoshida; Yujin E. Nakagawa (Advances in Astronomy)
We are developing and operating the automatic telescope Aoyama Gakuin University Robotic Optical Monitor for Astrophysical objects (AROMA) in the Sagamihara Campus of Aoyama Gakuin University. AROMA is composed of two observational equipments, AROMA-N and AROMA-W. AROMA-N is a 30-cm aperture telescope system for rapid follow-up observations of the optical afterglow of gamma-ray bursts. Automatic analysis pipeline for AROMA-N has been developed and is working. The other observational equipment AROMA-W is a wide-field observation system using multiple digital single-lens reflex cameras. It covers a large FOV of about 35∘×25∘. AROMAW provides photometric data in four bands with a limiting V magnitude of about 12-13 mag. Software to analyze massive image data automatically is being developed. We plan to monitor the luminosities of all the stars in the FOV of AROMA-W, detect optical transients, and trigger a follow-up observation with AROMA-N. We report on the development status and observational results of AROMA.